Peningkatan Keamanan Kunci Vigenère Menggunakan Steganografi Least Significant Bit (LSB) pada Sistem IoT Smart Door QR Code - Kasliono Kasliono; Syamsul Bahri; Dwi Marisa Midyanti; Muhammad Dito Asrofa; Riski Arasyid (Journal of Information System Research (JOSH), 2026)
In an increasingly connected digital era, the Internet of Things (IoT) enables seamless real-time data exchange across devices but also introduces critical challenges in data security. Although symmetric cryptography is widely adopted for its computational efficiency, key distribution and protection remain major vulnerabilities. This study aims to enhance IoT network security by integrating the Vigenère Cipher with Least Significant Bit (LSB) steganography. The LSB method is employed to conceal cryptographic keys within digital media, reducing the risk of unauthorized key interception. The proposed system is evaluated across three communication channels: the server, the user web interface, and ESP32/ESP32-CAM devices. Sniffing attack tests confirm that all transmitted data appears only as ciphertext, indicating successful protection of plaintext and secure key exchange. Performance measurements also demonstrate that the combined methods operate efficiently. On the server, encryption and encode require an average of 0.14 ms, while decode and decryption on the user web interface require 0.13 ms. On the ESP32-CAM, encryption and encode average 2.22 ms, with decode and decryption on the server requiring 0.10 ms. For the ESP32, server-side encryption and encode take 0.10 ms, while device-side decode and decryption take 1.46 ms. Overall, the integration of Vigenère Cipher and LSB steganography effectively improves data security in IoT communication without significantly impacting system performance.